2019
DOI: 10.1063/1.5084965
|View full text |Cite
|
Sign up to set email alerts
|

Observing microscopic transitions from macroscopic bursts: Instability-mediated resetting in the incoherent regime of the D-dimensional generalized Kuramoto model

Abstract: This paper considers a recently introduced D-dimensional generalized Kuramoto model for many (N 1) interacting agents in which the agents states are D-dimensional unit vectors. It was previously shown that, for even (but not odd) D, similar to the original Kuramoto model (D = 2), there exists a continuous dynamical phase transition from incoherence to coherence of the time asymptotic attracting state (time t → ∞) as the coupling parameter K increases through a critical value which we denote K (+) c > 0. We con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…41 demonstrated that the Kuramoto model generalized to even dimensions D ≥ 4 exhibits the unusual behavior of Instability-Mediated Resetting: If the coupling strength K is increased abruptly while remaining below the critical coupling strength for the onset to coherence, the Kuramoto model displays a short burst of coherence (see Ref. 41 for further details). This is illustrated by the results shown in Fig.…”
Section: B Applications Of Eq (15) To Previous Results On the Genermentioning
confidence: 99%
See 1 more Smart Citation
“…41 demonstrated that the Kuramoto model generalized to even dimensions D ≥ 4 exhibits the unusual behavior of Instability-Mediated Resetting: If the coupling strength K is increased abruptly while remaining below the critical coupling strength for the onset to coherence, the Kuramoto model displays a short burst of coherence (see Ref. 41 for further details). This is illustrated by the results shown in Fig.…”
Section: B Applications Of Eq (15) To Previous Results On the Genermentioning
confidence: 99%
“…In two recent papers 40,41 , we constructed a generalization of the Kuramoto model to D dimensions. Here we consider an even more general setup, where we consider a generalization to Eq.…”
Section: Generalizing Kuramoto-like Agents To Higher Dimensionsmentioning
confidence: 99%
“…The first-order model (2) and (4) have been extensively studied by several groups, to name a few, Frouvelle and Liu [16], Ha [7,19,21], Lohe [26,27], Markdahl [29,30], Olfati-Saber [32], Ott [5,6], Piccoli [4] and Zhu [39,40]. Below, we present brief literature review.…”
Section: 1mentioning
confidence: 99%
“…First, without loss of generality, we can set F (y ∞ i ) = 0 and ∇F (y ∞ i ) = 0, by settingF (x) := F (x) − F (y ∞ i ) which also implies ∇F (y ∞ i ) = ∇F (y ∞ i ). For a small positive number ε ∈ (0, 1) which will be determined later in (6) and 8, we associate the energy functional to the system…”
Section: 1mentioning
confidence: 99%
“…We review the swarming model (1) which has been extensively studied in diverse scientific disciplines: applied mathematics [5,11,13,22,26,27,29], applied physics [8,9,32,33,34,45,46] and engineering [35,36,37,38]. Since most of the work considered the homogeneous case Ω i ≡ O, we restrict ourselves to the homogeneous case at this moment.…”
mentioning
confidence: 99%